Optimasi Portofolio Saham Indeks Bisnis 27 Menggunakan Model Black Litterman Disertai Perhitungan Value At Risk: Bahasa Indonesia - Melasarah Deswita Rahmadi; Lailany Yahya; Agusyarif Rezka Nuha (Jurnal Matematika, Statistika dan Komputasi, 2024)
An investment can provide a profit with a certain level of risk for an investor both now and in the future. This indicates that investments are important in both financial and asset management. Finance investments can be made on several stocks or portfolios. To profit from an investment, you need a tool to optimize profit and risk, which is a portfolio. This research uses the Black Litterman Model in portfolio optimization along with Value at Risk (VaR) calculations to determine the risk of each stock. The data used is close price data on the Business Index 27 for the period January-December 2023. Next, selected 9 shares in the formation of an optimal portfolio namely, AKRA, AMRT, ASII, BBCA, BBNI, BBRI, INKP, KLBF and TLKM. Based on the calculations, the rate of profit achieved on the portfolio is 5.48% with a risk of 0.40%. Then use the Historical Method and the Monte Carlo Simulation Method to calculate the VaR using nine optimal stocks, with a 95% confidence rate. In the Monte Carlo simulation, 300 repetitions of VaR calculations are performed. Different results on both methods are due to different approaches to risk calculation